Pengaruh Good Corporate Governance Terhadap Environmental Disclosure - Eny Suprapti; Farhan Achmad Fajari; Achmad Syaiful Hidayat Anwar (Akuntabilitas, 2019)
Environmental problems become things that have not been considered for the companies. This Study aims to determine the effect good corporate governance to environmental disclosure. Good Corporate Governance is a system to controlling management, where GCG is proxied by the board of directors, board of commissioners, institutional ownership, managerial ownership, and audit committee. This reaserch use non financial companies listed on BEI. The research sample 30 companies. Measurement of environmental disclosure uses GRI – G4 index is 34 index.  This study using multiple regression. Based on the results of the study found good corporate governanceis proxieduse board of directors and board commissioners there isn’teffect on environmental disclosure.The results institutional ownership, managerial ownership, and audit committee effect on environemental disclosure